Particle physics at the European Spallation Source - Abele, H.; Degenkolb, Skyler; Schmidt, Ulrich (Physics reports, 2023)
Presently under construction in Lund, Sweden, the European Spallation Source (ESS) will be the world’s brightest neutron source. As such, it has the potential for a particle physics program with a unique reach and which is complementary to that available at other facilities. This paper describes proposed particle physics activities for the ESS. These encompass the exploitation of both the neutrons and neutrinos produced at the ESS for high precision (sensitivity) measurements (searches).
Elektronische Reproduktion der Druckausgabe: online verfügbar: 28. Juli 2023
Gesehen am 15.11.2023